Differential onset time of mirtazapine on pruritus and depression in a patient receiving hemodialysis. (January 2021) - Miyahara, Yu; Haruta-Tsukamoto, Ayaka; Funahashi, Hideki; Matsuo, Hisae; Kanemaru-Kawazoe, Anna; Nishimori, Toshikazu; Ishida, Yasushi
A 63-year-old male receiving hemodialysis for renal insufficiency developed severe and widespread pruritus, which was unresponsive to antihistamines and severe depression with insomnia, agitation, and anxiety. The oral administration of 7.5 mg mirtazapine daily alleviated his severe pruritus after 4 days and severe depression after 14 days. Mirtazapine has potential as a therapeutic option for patients receiving hemodialysis with depressive disorder and severe pruritus unresponsive to antihistamines.